TRADISI KESENIAN BUDAYA JARANAN PUTRO JATI PADA MASYARAKAT DI KOTA PALEMBANG - Gilang ardiansyah; Otoman; Santosa (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2026)
ABSTRACK This study describes the history of the entry of Jaranan culture in Palembang City and the cultural mixing of Jaranan art that occurred in the people of Palembang City. The data used in this study is qualitative data. The main points in this study are: First, the origin of the entry of Jaranan art in the city of Palembang and the process of its art. Second, about the acculturation of the mixing of foreign cultures, especially in the Jaranan art culture to the local culture in the community in the city of Palembang. The purpose of this study is to analyze how the origin of the entry of foreign cultures occurred due to the acculturation process in Jaranan art. The concept used is the concept of cultural acculturation which has five aspects that affect the process of cultural mixing, namely: adisi, syncretism, substitution, deculturation and rejection. The results of this study show that cultural mixing in Jaranan art also occurs due to the collision of the culture of marriage tradition with the culture of Jaranan art. In this case, Wedding traditions involve organ music and additional musical instruments such as drums and bass. The addition of these musical instruments creates cultural interaction, where traditional Palembang songs are played with the rhythm of Jaranan, so that it becomes an important part of Jaranan music. All of these elements work together to form a new entity that is the result of the merger of the culture of marriage and Jaranan.